Analyzing the Layout of Long-Term Care Facilities: A Psycho-Spatial Approach. (April 2022) - Rom, Yifat; Palgi, Yuval; Isaacson, Michal
When planning long-term care facilities (LTCFs), architects strive to design buildings that support high well-being (WB) levels for those who live and work in them. To achieve this goal, architects must understand what defines WB in old age and how these qualities can be achieved through the designed physical layout. This task must be achieved while tackling additional challenges, such as considering the official planning guidelines, codes, and additional requests given by the client. During the planning process, architects use their subjective impressions by visiting similar institutions, their personal experience as architects, and their subjective assumptions on what residents and caregivers may consider desirable. Once built, there are a lack of methodological ways to evaluate an existing LTCF unit's plan as a supportive tool for higher levels of WB. The current study aims to create a methodological tool to analyze LTCF units' layout, giving scores to each plan based on five aspects of WB that they support. In our article, we demonstrate this methodology's application on 40 plans of LTCFs, demonstrating its effectiveness. We believe that the approach presented in this article will contribute to furthering the quality of planning of LTCFs benefiting residents and caregivers alike.